From hope to horror diplomacy and the making of the Rwanda genocide - Leader, Joyce E. 1942- (ADST-DACOR diplomats and diplomacy series, 2020)
"Former ambassador Joyce Leader was DCM in Kigali from 1991 until the genocide erupted in 1994 and is a recognized authority on the failed diplomatic efforts to avert the tragedy"--